COVID-19 Outcomes Stratified by Control Status of Hypertension and Diabetes: Preliminary Findings From PCORnet, U.S. - Sandra L. Jackson, PhD; Jason P. Block, MD, MPH; Deborah B. Rolka, MS; Meda E. Pavkov, MD, PhD; Jennifer R. Chevinsky, MD; Akaki Lekiachvili, MD, MBA; Thomas W. Carton, PhD, MS; Deepika Thacker, MD; Joshua L. Denson, MD; Anuradha Paranjape, MD, MPH; Michael D. Kappelman, MD, MPH; Tegan K. Boehmer, PhD, MPH; et al. (Elsevier, 2022)
Introduction: Hypertension and diabetes are associated with increased COVID-19 severity, yet less is known about COVID-19 outcomes across levels of disease control for these conditions. Methods: All adults aged ≥20 years with COVID-19 between March 1, 2020 and March 15, 2021 in 42 healthcare systems in National Patient-Centered Clinical Research Network were identified. Results: Among 656,049 adults with COVID-19, 41% had hypertension, and 13% had diabetes. Of patients with classifiable hypertension, 35% had blood pressure <130/80 mmHg, 40% had blood pressure of 130‒139/80‒89 mmHg, 21% had blood pressure of 140‒159/90‒99 mmHg, and 6% had blood pressure ≥160/100 mmHg. Severe COVID-19 outcomes were more prevalent among those with blood pressure of ≥160/100 than among those with blood pressure of 130-139/80-89, including hospitalization (23.7% [95% CI=23.0, 24.4] vs 11.7% [95% CI=11.5, 11.9]), receipt of critical care (5.5% [95% CI=5.0, 5.8] vs 2.4% [95% CI=2.3, 2.5]), receipt of mechanical ventilation (3.0% [95% CI=2.7, 3.3] vs 1.2% [95% CI=1.1, 1.3]), and 60-day mortality (4.6% [95% CI=4.2, 4.9] vs 1.8% [95% CI=1.7, 1.9]). Of patients with classifiable diabetes, 44% had HbA1c <7%, 35% had HbA1c 7% to <9%, and 21% had HbA1c ≥9%. Hospitalization prevalence was 31.3% (95% CI=30.7, 31.9) among those with HbA1c <7% vs 40.2% (95% CI=39.4, 41.1) among those with HbA1c ≥9%; other outcomes did not differ substantially by HbA1c. Conclusions: These findings highlight the importance of appropriate management of hypertension and diabetes, including during public health emergencies such as the COVID-19 pandemic.